The Politics of HIV/AIDS in Africa: Ugandan HIV/AIDS Prevention Policy in Conflict with the Western Prevention Policies - Ibe, Anthony Chiwuba (Studia Bioethica, 2013)
Uganda had the highest HIV/AIDS prevalence in the world. Between the late 1980s and 1990s, at a time when HIV/AIDS was well on its way toward ravaging Sub-Saharan Africa, Uganda achieved an extraordinary feat by lowering the rate of HIV prevalence in Uganda by 70%. It stopped the spread of HIV/AIDS and the nation’s rate of infection was plummeted. Thus Uganda became a model of successful HIV/AIDS prevention for Africa and the world in general. As words of the “Uganda miracle” spread, journalists, researchers, policymakers and advocates all descended to ascertain how Uganda’s dramatic decline in HIV prevalence was accomplished, since Policymakers around the world look up to Uganda as a role model in the fight against HIV/AIDS. The question is What happened in Uganda?